A thematic analysis of the prevention of future deaths reports in healthcare from HM coroners in England and Wales 2016–2019. Issue 1 (February 2021) - Leary, Alison; Bushe, David; Oldman, Crystal; Lawler, Jessica; Punshon, Geoffrey
Background: The Coroners and Justice Act allows coroners in England or Wales to issue reports after inquest, if they believe that action should be taken to prevent a future death. Coroners are under a statutory duty to issue a Prevention of Future Death (PFD) report to persons or organisations that they believe have the power to act. Cumulatively, these reports may contain useful intelligence for patient safety. The aim of this study was to examine the feasibility of extracting data from these reports and to evaluate if learning was possible from any common themes. Methods: Reports were extracted from 2016 to 2019 for deaths in hospitals, care homes and the community in England and Wales. These were subjected to descriptive statistics and thematic analysis of coroner's concerns. Application of data mining techniques was not possible due to data quality. Results: 710 reports were examined, with 3469 concerns being raised (mean 4.88, range 1–33). 36 reports expressed concern about having to issue repeat PFDs to the same organisation for the same or similar concerns. Thematic analysis reliability was high ( κ 0.89 unweighted) with five emerging primary themes: deficit in skill or knowledge, missed, delayed or uncoordinated care, communication and cultural issues, systems issues and lack of resources. A codebook of 53 subthemes were identified. Conclusions: PFD reports offer valuable insight. Aggregation and continued analysis of these reports could offer more informed patient safety, workforce development and organisational policy. Improved data quality would allow for possible automation of analysis and faster feedback into practice.